Heavy‐Atom Tunneling Calculations in Thirteen Organic Reactions: Tunneling Contributions are Substantial, and Bell's Formula Closely Approximates Multidimensional Tunneling at ≥250 K. Issue 42 (18th September 2017) - Doubleday, Charles; Armas, Randy; Walker, Dana; Cosgriff, Christopher V.; Greer, Edyta M.
Abstract: Multidimensional tunneling calculations are carried out for 13 reactions, to test the scope of heavy‐atom tunneling in organic chemistry, and to check the accuracy of one‐dimensional tunneling models. The reactions include pericyclic, cycloaromatization, radical cyclization and ring opening, and SN 2. When compared at the temperatures that give the same effective rate constant of 3×10 −5 s −1, tunneling accounts for 25–95 % of the rate in 8 of the 13 reactions. Values of transmission coefficients predicted by Bell's formula, κBell , agree well with multidimensional tunneling (canonical variational transition state theory with small curvature tunneling), κSCT . Mean unsigned deviations of κBell vs. κSCT are 0.08, 0.04, 0.02 at 250, 300 and 400 K. This suggests that κBell is a useful first choice for predicting transmission coefficients in heavy‐atom tunnelling. Abstract : Several common reaction types were studied to assess the importance of heavy‐atom tunneling in organic reactions. The results are consistent with the hypothesis that heavy‐atom tunneling is widespread. The success of Bell's formula suggests it is a useful first choice for predicting transmission coefficients in heavy‐atom tunnelling.